Is serum hornerin a potential biomarker in fibromyalgia? A pilot study - Seyithanoğlu Muhammed; Koca Tuba Tülay; Dağlı Hasan; Ertürk Zeynel (Türk Biyokimya Dergisi)
The study aims to investigate the relationship between serum hornerin levels and disease severity and pain scores and to evaluate hornerin’s potential as a biomarker and its role in understanding the etiopathogenesis of fibromyalgia (FM).